Dancing Rupestres: : the radical of the body in intentional aesthetic movement - Guilherme, Sylviane; Sousa Fernandes, Silvia Aparecida de (Revista Brasileira de Estudos da Presença, 2022)
The text presents a critical analysis of the roots of dance from the perspective of historical and dialectical materialism, the formulations of Marx and Engels, and of the Marxist aesthetes who followed them, proposing a study of the concept, reason and purpose of dance for the human race. It approaches themes such as work as the founding category of the human being. It then discusses human body movement as free creation work, intentional body movements of work and the process of their transition into dance movements. Finally, based on studies on human manifestations developed on the aesthetic level, it shows how the human being arrived at dance as art.